POSSIBILITIES FOR PRESENTING THE LATGALIAN LANGUAGE MATERIAL IN THE TRANSLATING TRILINGUAL DICTIONARIES - Leikuma, Lidija (Via Latgalica, 2013)
The article presents the conclusions the author has come to during the implementation of the project “Development of Research Infrastructure for Education in the Humanities in Eastern Latvia, Lithuania”) the code name of which is “LLIII-207 HipiLatLit”. On the basis of 1,000,000 (one million) word usage instances of “Frequency Dictionary of the Written Sources of the Lithuanian Language” (“Dažninis rašytinės lietuvių kalbos žodynas” (Compiler A. Utka; http://donelaitis.vdu.lt/publikacijos/Dazninis_zodynas.pdf) an original translating dictionary containing 10,000 units has been compiled. For the most frequently used words of the base (Lithuanian) language the counterparts have been given in the two standardised variants of the Latvian language – the Latvian literary language and the Latgalian written or literary language. The ways of searching and possibilities of fi nding the equivalents are shown by the insight into the laboratory of creation of the electronic “Lithuanian-Latvian- Latgalian Dictionary”, focusing on the Latgalian part of the dictionary in more detail. Since a wide-scale and linguistically correct collection of the Latgalian vocabulary is still not available, in the process of the development of the dictionary it was necessary to deal with a number of theoretical and practical problems. For solving of these problems the conclusions of the Latvian (Alīse Laua, Ruta Veidemane, Liene Roze, Inta Freimane) and non-Latvian (Valery Berkov, Vladimir Dubichinski, Evalda Jakaitienė) lexicologists and lexicographers have been applied. In the project much has been done for clearing up and specifying the semantic counterparts of the base language in accordance with the qualities of the corpus. The linguistic processing of the selected lexemes and homogeneous interpretation of the material needed multiple checking of the material as it is given in dictionaries and scrupulous comparison. The semantic structure coincides for unambiguous words, i.e. vocabulary of general use, for other cases translating and explaining equivalents have been searched for. Nowadays not everything corresponds any longer to the recordings in the earlier lexicographic sources (“The Lithuanian-Latvian dictionary” (1995), “The Latvian Literary Language Dictionary” (1972–1996)) – the languages have been changing. Also the Latgalian part of the dictionary presents the changes of the lexical composition and word meanings. It has been tried to display it with appropriate markings as to the restrictions of the word usage. Although in the Latgalian language at times there are no necessary terms or names for the abstract concepts, however, it is possible to find the necessary counterparts for everything. The lexicographic finish of the material enclosed is explained in more detail. The most important dictionaries for the project under implementation have been actualised. Up to now, two translating trilingual dictionaries have been published (Jānis Kurmins “Słownik polsko łacinsko łotewski” (1858) and Eduards Kozlovskis “Krìwu- Latgališu-Wòcu wòrdinica” (1918)) where one of the languages is Latgalian; topical entries of these dictionaries have been dealt with in more detail. Also other developments have been analysed, namely those containing the Latgalian vocabulary, critical comments being given on potential neologisms, namely nonce-words. The majority of the collections of the Latgalian vocabulary are not extensive, and their producers have generally not been the Baltic linguists. The two former lexicographic sources have a normative nature: Pīters Strods “Pareizraksteibas vōrdneica" (1933) and Mikelis Bukšs and Juris Placinskis “Latgaļu volūdas gramatika un pareizraksteibas vōrdneica” (1973). In selecting the Latgalian counterparts for the new dictionary both the former normative sources have been taken into account and traditions have been observed, the area of the usage of lexemes, the significance of the word or the form, the frequency of the usage, etc. have been respected. The possibilities of the Latgalian language to present the semantic counterparts for the relevant lexemes of the Lithuanian and Latvian languages have been characterised in more detail. In compliance with the base language both the equivalent Latgalian vocabulary and that one having no direct equivalent have been shown, the principles for selection of synonyms and word variants have been explained, the necessity of inclusion of the word variants in the translating dictionary has been substantiated. The less the language has been cultivated, the higher number of variants it has, although the option of choice of variants is unsatisfactory mostly for practitioners. Some uncertainty in the Latgalian language at the moment is inevitable: due to uncertain status of the language and the variable use as regards the intensity of utilisation, the language has been standardised and codified deficiently up to now. In this article a special attention has been paid to the analysis of the very material of the Latgalian language, to the synonyms of the Latgalian equivalents, the explanations as regards indications of the restrictions on the word usage. Occasionally more detailed comments have been given for the relevant examples. Due to the rich use of marking “The Lithuanian-Latvian-Latgalian Dictionary” differs from the traditional translating dictionaries where appropriate signs are used less frequently, however, cultivation of the language is promoted just by evaluation of the vocabulary layers, analysis of potentials, predictions of the further changes. Such problem situations as, for example, usefulness of inclusion of a greater number of Slavisms, a lack of consequence as to indications of the stylistic shade of colloquial speech, the uncertain coherence between the colloquialisms and barbarisms have been discussed in the article. The place of the literarisms has been dealt with in the system of the Latgalian language, their fitting and “inevitability" nowadays have been analysed. Some of the uncertainties remained in the development of the dictionary have been outlined. Evaluation has also been provided for the selection of the Latgalian vocabulary, thus giving new, clearer and more certain impulses as to the content for cultivators of the Latgalian language. The compiled electronic “Lithuanian-Latvian-Latgalian Dictionary” will be useful both for practical use and research in lexicology and lexicography. Its Latgalian part can be used as a basis for the further lexicographic developments.